Measurable Fishing as An Attempt of Preventing Overfishing Phenomenon in Indonesian Waters - Kholis Roisah; Rahayu Rahayu; Peni Susetyorini; Arnanda Yusliwidaka; Saidatul Nadia Abd Aziz (Lex Scientia Law Review, 2024)
This research focuses on analyzing the effectiveness of the provision about the measurable fishing as specified in the Government Regulation Number 11 of 2023 as an attempt of preventing overfishing and maintaining the sustainability of biodiversity in Indonesian waters and sea territory. This study is a normative research with statute approach. The data used was secondary one consisting of primary legal, secondary legal, and non-legal materials. Overfishing phenomenon is a serious problem endangering ocean resource and environment. Some countries have reported the overfishing problems damaging the sea ecosystem. Indonesia is one of countries predictably encountering overfishing phenomenon, particularly in northern Java water territory. The indicators of overfishing phenomenon are smaller size of fish and fewer fish caught requiring the fishermen to go farther to catch fish. The fact of overfishing leads to a policy about zone-based measurable fishing and catching quota. This policy can cease overfishing phenomenon because it can control and monitor fish catch, and thereby makes resource and environment better in water or sea territory. Considering the conclusion of research, the concept of measurable fishing formulated by Indonesia is based on zone and quota. Zone base prioritize equal share for the fishermen, promotes economic growth, and determines the capacity of catch allowed for a certain species, while quota base focuses on the limitation of fish catching level based on the potency of fish caught that can control the fishing rate according to the fish resource.